Α-[11C]-methyl-L-tryptophan PET for tracer localization of epileptogenic brain regions: clinical studies. (October 2011) - Kumar, Ajay; Asano, Eishi; Chugani, Harry T
Of several molecular probes used in PET, only α-[ 11 C]-methyl-L -tryptophan (AMT) is able to pinpoint the epileptic focus itself in the interictal state, by revealing a focus of increased AMT uptake, even when an MRI or glucose metabolism PET demonstrates normal findings. AMT PET appears to be particularly useful in patients with tuberous sclerosis complex and in patients with cortical developmental malformations. Although the sensitivity of AMT PET in finding the epileptic focus is about 70%, its specificity is almost 100%, indicating that if AMT PET identifies an area of increased uptake, it likely represents the epileptic focus which needs to be resected for better surgical outcome. In nontuberous sclerosis complex patients with cortical dysplasia, increased AMT uptake is usually associated with cortical dysplasia type IIB and a very good surgical outcome. Previously, no imaging modality has been able to predict the exact pathology subtype or differentiate between epileptogenic and nonepileptogenic lesions interictally. The neuropathological similarities between tubers and type IIB cortical dysplasia suggest a common mechanism of epilepsy, for which AMT PET is a biomarker. Due to the limited access to AMT PET, as presently it is labeled with 11 C, which has a half-life of only 20 min and therefore has to be synthesized on site using a cyclotron, most of the AMT experience has originated primarily from only two centers. Therefore, there is a need for more clinical studies from other centers and this can be greatly facilitated if AMT can be labeled with 18 F, a PET radionuclide widely available with a half-life of 110 min.